Research on the Combustion Performance of Mixed Charge of the Super-porous Coated Propellant. (August 2020) - Xiang, Cao; Lina, Zhang; Ping, Du; Shuai, Jiang; Fengqiang, Nan
Abstract: In order to study the constant volume combustion performance of the mixed charge of super-porous propellant and super-porous coated propellant, 37-hole nitroguanidine propellant and 37-hole nitroguanidine coated propellant containing flame retardant TiO2 were prepared. At high temperature(50°C), normal temperature(20°C), low temperature(-40°C), a constant volume combustion experiment was performed on a mixed charge with a mass ratio of 1: 1 for the 37-hole propellant and the 37-hole coated propellant. The research results show that the constant volume combustion performance of the mixed charge is different from a single coated propellant and a single base propellant. The p-t, dp/dt-t and L-B curves of the mixed charge were between the coated propellant and the base propellant, but mixed charge has the greatest progressive combustion. And the temperature dependence of the progressive combustion of mixed charge is small, which has a certain low temperature effect.